SIMULATION AND EXPERIMENTAL RESEARCH ON AN AIR CONTROLLED FAULT BELT CONVEYOR - KANG WenLong; YANG LiGuo (Jixie qiangdu)
According to the long response time and can not achieve the bidirectional arrest of broken-belt catching device,broken-belt catching device with function of pneumatic control、vaulted arrest end and bidirectional arrest was proposed. The structure and working principle of catching device were explained. The arrest process of catching device was analyzed by using virtual prototype technology. The 1:2 experimental model of catching device was made by using the similarity theory. Feasibility of catching device was testified by experiment. The response time and catching force of the design model of catching device were obtained by using the dimensional analysis method. The results show that the contact between arrest plate and belt product little jitter, and has no effect on the catching results. The response time of the design model of catching device is 0.5 s. The catching force is 24.768 kN, and has little damage on the belt.